Determinants of Customer Loyalty For Liquid Petroleum Gas (LPG) and Bio-Cng Products: A Case Study in West Nusa Tenggara - Prirafianti; Sumarwan, Ujang; Aminah, Mimin (Jurnal Manajemen & Agribisnis, 2023)
One of the new renewable energy that can replace Liquid Petroleum Gas (LPG) is by maximizing the utilization of Biogas which modifies it to become Bio-Compressed Natural Gas or Bio-CNG on a commercial scale, especially for cooking. This study aims to answer two main objectives. The first is to find out the loyalty of LPG customers, the level of interest in Bio-CNG products to commercial sector business actors, and the second is to find out market testing that is influenced by price, product quality, and service quality on interest in buying Bio-CNG. The research was conducted from January to March 2022. The data collected in this study were primary data obtained from an Indonesian-language questionnaire survey which was distributed via the Google form link using the Ordinal scale. The sampling method (respondents) used was purposive sampling. Data is processed and analyzed using Logistic Regression Analysis. The research results obtained 100 respondents and showed that all variables had a significant influence on Horeka's interest in switching to using Bio-CNG. This research provides an overview and insight into the factors that influence the interest in buying Bio-CNG products among hospitality businesses. This research provides an overview and insight into the factors that influence the interest in buying Bio-CNG products among hospitality businesses. As consumers or in this research, hospitality business actors, they want to get good service from providers or sellers of Bio-CNG fuel products. As a provider of Bio-CNG fuel products, of course, you have to think about the quality of its service to hospitality businesses. Keywords: Bio-CNG, customer loyalty, market tests